Urinary Tract Drainage Selection in Case of Pyelonephritis in Pregnant Women - L. A. Sinyakova; O. B. Loran; I. V. Kosova; D. N. Kolbasov; H. B. Tsitsaev (Вестник урологии, 2020)
The article presents an analysis of the treatment results of 1122 patients with pyelonephritis in pregnancy at different gestational periods (from 6 to 39-40 weeks of pregnancy). The age of the patients was from 16 to 41 years, the average age was 26.15 ± 7 years. The indications and methods of urinary tract drainage in pregnant women were analyzed depending on the causes of urodynamic disturbances (kidney stone disease, decreased urinary tract tone, ureters compression by the uterus, vesico-urethral reflux) pregnancy term; pyelonephritis in pregnancy stage (serous/ purulent). Errors in the patients’ management after purulent pyelonephritis in pregnancy are considered. The expediency of examining and treating patients with risk factors for urinary tract infections during pregnancy were indicated at the stage of preparing a woman for pregnancy. Antegrade draining of the urinary tract is indicated for pregnant women from the 31st pregnancy week (and even shorter periods with a pronounced violation of urodynamics) with the presence of knee-shaped deviation in the ureter`s upper third and with suspected purulent process. Therefore, nephrostomy draining provides a more adequate outflow of urine from the affected kidney and makes it possible to control daily diuresis. It is necessary to conduct active monitoring of pregnant women with the presence of internal ureteral stents and their timely replacement. It is advisable to remove the drainage 3-4 weeks after birth, depending on the causes of the urodynamics` disorders. Symptom build-up dynamics, severity of intoxication, multi-organ lesion, the possibility of antenatal death of the fetus require urgent choice of the method of urinary tract drainage and the early initiation of intensive therapy in patients with suspected purulent process. Antimicrobial therapy should be carried out in accordance with the Russian guidelines on Urinary tract infections.TThe study did not have sponsorship. The authors have declared no conflicts of interest.